Uganda : Staff Report for the 2015 Article IV Consultation and Fourth Review Under the Policy Support Instrument. (IMF Staff Country Reports; Country Report, 2015)
This 2015 Article IV Consultation highlights that Uganda's recent economic performance has been favorable. Real GDP growth is projected at 5.24 percent for FY2014/15 supported by a fiscal stimulus and a recovery in private consumption. Annual core inflation increased to 4.75 percent in May, from very depressed levels, mainly fueled by the shilling depreciation pass-through. The current account deficit is set to widen to about 9 percent of GDP reflecting increasing capital goods imports, but international reserves remain adequate. The outlook is promising. Growth is estimated at 5.75 percent in FY2015/16 and an average 6.25 percent over the medium-term.